2021
DOI: 10.1038/s41598-021-82792-2
|View full text |Cite
|
Sign up to set email alerts
|

Rat in vitro spermatogenesis promoted by chemical supplementations and oxygen-tension control

Abstract: In vitro spermatogenesis (IVS) using air–liquid interphase organ culture method is possible with mouse testis tissues. The same method, however, has been hardly applicable to animals other than mice, only producing no or limited progression of spermatogenesis. In the present study, we challenged IVS of rats with modifications of culture medium, by supplementing chemical substances, including hormones, antioxidants, and lysophospholipids. In addition, reducing oxygen tension by placing tissues in an incubator o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(53 citation statements)
references
References 55 publications
1
50
2
Order By: Relevance
“…Male rPGCLCs that aggregated with male gonadal somatic cells lost Nanos3-T2A-tdTomato expression by day 3 (fig. S6, A and B), indicating the need for further optimization, as has recently been demonstrated for organ culture of neonatal rat testes ( 16 ). By contrast, female gonadal somatic cells could support the survival of male N3T + rPGCLCs (fig.…”
mentioning
confidence: 84%
“…Male rPGCLCs that aggregated with male gonadal somatic cells lost Nanos3-T2A-tdTomato expression by day 3 (fig. S6, A and B), indicating the need for further optimization, as has recently been demonstrated for organ culture of neonatal rat testes ( 16 ). By contrast, female gonadal somatic cells could support the survival of male N3T + rPGCLCs (fig.…”
mentioning
confidence: 84%
“…Although more tubules showed DNA fragmentation when comparing in vitro to in vivo conditions, few pachytene spermatocytes were TUNEL positive, suggesting that apoptosis occurred after this stage. Two previous studies have reported that round spermatids could be obtained after in vitro maturation of rat prepubertal testes, albeit in very small proportions [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The further development and optimization of organotypic culture procedures in animal models is essential before a human application can be envisaged. The rat model, the spermatogenesis of which has a duration that is intermediate between mice and humans (53 days vs. 36 and 74 days), and shows (as in humans) a germ cell maturation arrest in organotypic cultures [ 13 , 14 , 15 , 16 , 17 , 18 ], appears to be a relevant model for the improvement of in vitro culture conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Dumont et al used retinol (vitamin A) to culture mouse prepubertal testicular tissue and found an improvement in the differentiation of SSCs into motile spermatozoa after culturing for 30 days [ 157 ]. Interestingly, IVS was improved in rats by supplementing the culture medium with hormones (testosterone, thyroxin, FSH, and LH), antioxidants (glutathione and ascorbic acid), and lysophospholipids ( l -a-Lysophosphatidylcholine and lysophosphatidylserine) under hypoxic culture conditions for 70 days [ 158 ]. Recently, retinoic acid in combination with stem cell factor (SCF) improved IVS and differentiation of SSCs in rats by upregulating PRTM1 , STRA8 , c- KIT , PIWIL2 , and OCT4 gene expression [ 159 ].…”
Section: Spermatogonial Stem Cell As New Option To Treat Impaired Spermatogenesismentioning
confidence: 99%